죽음준비교육 프로그램이 자원봉사자의 죽음불안과 삶의 의미에 미치는 효과 - 윤매옥; Yoon, Me-Ok (Han'guk Hosŭpʻisŭ Wanhwa Uiryo Hakhoe chi = The Korean journal of hospice and palliative care, 2009)
Purpose: The purpose of this study was to analyze the effect of death preparing education on death anxiety and meaning of life for volunteers. Methods: Data collection and intervention were carried out from January 11 to 25, 2009. The subjects included 60 volunteers in Jeonju city, and they were divided into two groups; 30 each of experimental group and control group. Death preparing education program contained 5 steps. Data were analyzed with t-test, $x^2$-test, and ANCOVA test with SPSS version 12.0. Results: The death anxiety scores in the experimental group were significantly lower than in the control group (F=4.01, P=0.046). The meaning of life scores in the experimental group were significantly higher than in the control group (F=6.32, P=0.015). Conclusion: The death preparing education program for volunteers was confirmed to be an effective intervention to lessen death anxiety and to improve the meaning of life. Therefore, I strongly recommend that this program should generously be applied to volunteers. 목적: 본 연구는 자원봉사자에게 죽음준비교육 프로그램을 제공하여 죽음불안과 삶의 의미에 미치는 효과를 검증하기 위하여 시도하였다. 방법: 자료수집기간은 2009년 1월 11일부터 25일까지 이루어졌다. 연구대상자는 전주시에 거주하는 자원봉사자로서 죽음준비의 목적과 내용을 소개하고 연구에 참여하고자 동의한 자로 실험군 30명, 대조군 30명으로 총 60명이었다. 죽음준비교육 프로그램은 총 5단계로, 도입단계에서 삶과 죽음의 이해, 수용단계에서 유서쓰기, 체험단계에서 입관, 나눔 단계에서 느낌 공유하기, 마무리단계에서 결단과 축복하기의 주제로 구성되어 있으며, 각 단계별 60분씩 실시하였다. 수집된 자료는 SPSS version 12.0을 사용하여 빈도, 백분율, 평균, 표준편차 등의 서술통계와 사전 동질성검증은 t-test, chi-square test를 실시하였고 가설검증을 위해 ANCOVA로 분석하였다. 결과: 죽음준비교육 프로그램을 제공받은 실험군은 제공받지 않은 대조군보다 죽음불안 정도가 통계적으로 유의하게 낮았다(F=4.01, P=0.046). 죽음준비교육 프로그램을 제공받은 실험군은 제공받지 않은 대조군보다 삶의 의미 정도가 통계적으로 유의하게 높았다(F=6.32, P=0.015). 결론: 죽음준비교육 프로그램은 죽음불안을 감소시키고 삶의 의미를 향상시키는데 효과적인 것으로 확인되었다. 따라서 죽음준비교육 프로그램은 자원봉사자의 죽음에 대한 불안을 감소시키고 삶의 의미 향상을 위해 활용될 수 있다고 사료되며, 좀 더 다양한 자원봉사자에게 확대 적용될 수 있기를 기대한다.